ANALISIS KRITIS PENGELOLAAN PERAIRAN PESISIR DAN PULAU-PULAU KECIL DI INDONESIA (STUDI PENGATURAN PENGELOLAAN PERAIRAN PESISIR DAN PULAU-PULAU KECIL PASCA LAHIRNYA UNDANG-UNDANG NO 1 TAHUN 2014 DAN UNDANG-UNDANG NO 23 TAHUN 2014) - ARIFIN, ZAENAL; SATRIA, ADHI PUTRA (Universitas Mahasaraswati Mataram, 2020)
This article aims to explain how the development of coastal waters and small islands management problems in Indonesia after the issue of Law No. 1 of 2014 and Law No. 23 of 2014, this paper uses normative juridical approach, where normative juridical research is research which uses primary data as main data in research. The results show that the development of management of coastal waters and small islands in Indonesia experience changes, especially when the issue of Law No. 1 of 2014 and Law No. 23 of 2014, these changes brought a new problem which include the loss of regional authority over management coastal waters, small islands, overlapping arrangements regarding Spatial Planning and Zoning Plans for Coastal Areas and Small Islands (RZWPPK), and Management and Utilization of marine resources is possible to be managed by foreign parties. So that the conclusions obtained is there is need to redesign the role of the city regional government in the management of coastal waters and small islands, removing the obligation of the local government to determine Spatial Planning and Zoning Plans for Coastal and Small Islands (RZWPPK) and protect and empower coastal communities in the management of coastal waters and small islands.